THE TALK AND ACTION IN THE STRUCTURES OF EXPECTATION SEEN IN Ã¢â‚¬Å“GREAT EXPECTATIONÃ¢â‚¬Â MOVIE - RIZKIANA MAHARDDHIKA; NOVI SRIWULANDARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
This study is aimed to investigate and analyze the kinds and functions of Talk and Action in the Structure of Expectation appeared in every conversation in Great Expectation movie. In this case, the researcher used the theory of Talk and Action by Ronald Wardaugh and the Structure of Expectation by Claire Kraimsch. The researcher formulated two research problems; (1) what kinds of talk and action used by main characters of the Great Expectation movie? , and (2) how much the frequency of structure of expectation used by main characters of the Great Expectation movie?. To answer those questions, first, the researcher described some intrinsic element of the movie, such as: setting, plot, synopsis of the movie, and nature of speech event. Then, the researcher started to analyze the pattern and kind of talk and action and the structure of expectation in every conversation in the movie by using a qualitative descriptive method. The findings show that there are some kinds of talk and action raised such as speech act, cooperation, and conversation. The researcher also found the pattern of expectation in main characters’ speech inside the movie.